2013
DOI: 10.3109/10826084.2013.841249
|View full text |Cite
|
Sign up to set email alerts
|

Substance Misuse Following Roux-en-Y Gastric Bypass Surgery

Abstract: Post-bariatric surgery patients are overrepresented in substance abuse treatment, particularly those who have had the Roux-en-Y gastric bypass (RYGB) procedure. The severity of the substance use disorder (SUD; i.e., warranting inpatient treatment) and related consequences necessitate a better understanding of the variables associated with post-RYGB SUDs. This investigation assessed factors associated with post-RYGB substance misuse. Post-RYGB patients (N = 141; at least 24 months postsurgery) completed an onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 59 publications
2
58
2
3
Order By: Relevance
“…This is even more important as RYGB operations are increasingly performed in patients with only moderate degrees of obesity, but severe and difficult-to-control metabolic disorders, as well as in adolescents without knowing the long-term consequences in these individuals. Finally, known negative side effects of RYGB [e.g., effects on bone metabolism, increased risk for drug abuse (112)] require intensive research efforts in the future.…”
Section: Discussionmentioning
confidence: 99%
“…This is even more important as RYGB operations are increasingly performed in patients with only moderate degrees of obesity, but severe and difficult-to-control metabolic disorders, as well as in adolescents without knowing the long-term consequences in these individuals. Finally, known negative side effects of RYGB [e.g., effects on bone metabolism, increased risk for drug abuse (112)] require intensive research efforts in the future.…”
Section: Discussionmentioning
confidence: 99%
“…It may be speculated whether food addiction substitutes or acts as a replacement for tobacco addiction or vice versa. Similarly, gastric bypass patients who had a higher YFAS symptom count before bariatric surgery (based on retrospective reports) were more likely to have post-bariatric substance misuse, suggesting a possible 'addiction transfer' [55]. A recent study reported a trend towards less alcohol use and associated problems in obese individuals with food addiction than in those without food addiction.…”
Section: Relationships With Other Constructs Not or Indirectly Relatementioning
confidence: 99%
“…Men progressed to alcohol dependency faster than women. In another study of 141 gastric bypass surgery patients at least 2 years post-surgery, 14 % fulfilled criteria for substance misuse disorder (tobacco, sedative, alcohol, cannabis and cocaine in descending relative frequency of use) [ 55 ]. Substance misuse was associated with poor weight loss and a family history of substance misuse as well as pre-operative food addiction, maladaptive eating behaviour, and heightened responsiveness to environmental food cues.…”
Section: Introductionmentioning
confidence: 98%